Efektivitas Media Flash Cards dalam Meningkatkan Kosakata Bahasa Inggris - Eka Fitriyani; Putri Zulmi Nulanda (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2017)
English proficiency is important because it gives a positive academic influence. English skills can be seen from the amount of vocabulary a person has. One of the creative efforts in learning to be attractive is using flash cards media. This study aims to determine whether flash cards media can improve the vocabulary of students in primary school. This research used quasi-experimental method with nonequivalent pretest-posttest control group design. The research subjects were 35 second grade students of elementary school, which were divided into two groups namely experimental group and control group. The hypothesis of this research is that there is a difference of vocabulary between experimental group and control group before and after giving flash cards media. The independent sample t-test of the gain score of the experimental group (11.7895) was higher than the control group (3.2500) with the 8,998 and sig t-counts 0.000 (p <0.01), meaning that there is significant difference between pretest-posttest experimental and control group. It shows that flash cards can improve students' English vocabulary.